Penerapan Good Corporate Governance - Endang Suriyani Munthe; Putri Ramadani; Salwa Latipah; Syairah Nasution; Ahmad Wahyudi zein (CV. ITTC INDONESIA, 2025)
The implementation of Good Corporate Governance (GCG) is a fundamental aspect in achieving sustainability and improving company performance amidst the increasingly complex dynamics of the business environment. GCG functions as a set of systems, principles, and mechanisms that regulate and control relationships between stakeholders to create healthy, transparent, and responsible company management. The main principles of GCG, namely transparency, accountability, responsibility, independence, and fairness, are an important foundation in ensuring that every company activity is carried out in accordance with regulations, business ethics, and the interests of all stakeholders. This study aims to assess the effectiveness of the implementation of Good Corporate Governance in supporting company performance and reputation. The research method used is a qualitative approach with a case study design, which allows researchers to gain an in-depth understanding of GCG practices in the real context of the organization. Data were collected through document analysis, observation, and interviews with relevant parties. The results of the study indicate that good GCG implementation can increase stakeholder trust, strengthen the internal control system, and minimize the potential for irregularities such as corruption, collusion, and nepotism. In addition, GCG implementation also contributes to creating more objective and long-term oriented decision-making. The Indonesian economic crisis of 1997–1998 was a crucial turning point in raising awareness of the urgency of implementing good corporate governance. The crisis exposed the weaknesses of corporate oversight and governance systems, thus recognizing GCG as a crucial strategy for building business sustainability and maintaining a company's reputation at the national and global levels.